Effects of dietary sodium reduction on blood pressure in subjects with resistant hypertension: results from a randomized trial - Pimenta, Eduardo; Gaddam, Krishna K; Oparil, Suzanne; Aban, Inmaculada; Husain, Saima; Dell'Italia, Louis J; Calhoun, David A (Hypertension (Dallas, Tex. 1979), 2009)
Observational studies indicate a significant relation between dietary sodium and level of blood pressure. However, the role of salt sensitivity in the development of resistant hypertension is unknown. The present study examined the effects of dietary salt restriction on office and 24-hour ambulatory blood pressure in subjects with resistant hypertension. Twelve subjects with resistant hypertension entered into a randomized crossover evaluation of low (50 mmol/24 hours x 7 days) and high sodium diets (250 mmol/24 hours x 7 days) separated by a 2-week washout period. Brain natriuretic peptide; plasma renin activity; 24-hour urinary aldosterone, sodium, and potassium; 24-hour ambulatory blood pressure monitoring; aortic pulse wave velocity; and augmentation index were compared between dietary treatment periods. At baseline, subjects were on an average of 3.4+/-0.5 antihypertensive medications with a mean office BP of 145.8+/-10.8/83.9+/-11.2 mm Hg. Mean urinary sodium excretion was 46.1+/-26.8 versus 252.2+/-64.6 mmol/24 hours during low- versus high-salt intake. Low- compared to high-salt diet decreased office systolic and diastolic blood pressure by 22.7 and 9.1 mm Hg, respectively. Plasma renin activity increased whereas brain natriuretic peptide and creatinine clearance decreased during low-salt intake, indicative of intravascular volume reduction. These results indicate that excessive dietary sodium ingestion contributes importantly to resistance to antihypertensive treatment. Strategies to substantially reduce dietary salt intake should be part of the overall treatment of resistant hypertension.